Difference sequence space (...) of fuzzy real numbers - Tripathy, Binod Chandra; Borgohain, Stuti (Mathematical Modelling and Analysis, 2008)
The difference sequence space of fuzzy real numbers for both 1 ≤ p < 8 and 0 < p < 1, is introduced. Some properties of this sequence space like solidness, symmetricity, convergence‐free are studied. Some inclusion relations involving this sequence space are obtained. First Published Online: 14 Oct 2010